2021
DOI: 10.1186/s13045-021-01098-y
|View full text |Cite
|
Sign up to set email alerts
|

A dual inhibitor overcomes drug-resistant FLT3-ITD acute myeloid leukemia

Abstract: FLT3 mutations are the most frequently identified genetic alterations in acute myeloid leukemia (AML) and are associated with poor prognosis. Multiple FLT3 inhibitors are in various stages of clinical evaluation. However, resistance to FLT3 inhibitors resulting from acquired point mutations in tyrosine kinase domain (TKD) have limited the sustained efficacy of treatments, and a “gatekeeper” mutation (F691L) is resistant to most available FLT3 inhibitors. Thus, new FLT3 inhibitors against both FLT3 internal tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In general, our findings suggest that KIM-161 could simultaneously inhibit signaling at multiple nodes originating from various tumor microenvironment cues. The direct target(s) of this compound has not been fully understood in as much as tirbanibulin is still revealing its polypharmacology nature ( Wang et al, 2021 ). Our work with KIM-161 proved that changes in the KX2-391 skeleton changes the cytotoxic profile from dual Src/tubulin inhibition to other targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, our findings suggest that KIM-161 could simultaneously inhibit signaling at multiple nodes originating from various tumor microenvironment cues. The direct target(s) of this compound has not been fully understood in as much as tirbanibulin is still revealing its polypharmacology nature ( Wang et al, 2021 ). Our work with KIM-161 proved that changes in the KX2-391 skeleton changes the cytotoxic profile from dual Src/tubulin inhibition to other targets.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is rare to find a clinically relevant kinase inhibitor that does not bind to other kinases, an approach commonly known as the polypharmacology (multi-targeted) kinase inhibitors ( Hartmann et al, 2009 ). KX2-391 itself was recently found to inhibit a mutated FLT3 kinase ( Wang et al, 2021 ). Therefore, we decided to investigate a change of the biphenyl core of KX series to a related system aiming to: a) study the SAR of KX scaffold extending beyond the biphenyl-4-( N -benzyl)acetamide scaffold (KX1-136, Figure 1B ), b) monitor the effect of replacing the outer ring of the biaryl system of KX series on kinase activities and specificities, and c) attempt to identify novel molecular leads with potent anticancer activities that are not necessarily dependent on Src/tubulin inhibition ( Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…Although rarely observed in AML patients, FLT3 gene F691L mutation shows universal resistance to all available FLT3 inhibitors. Therefore, F691L mutation becomes a crucial detection item for treatment decisions ( Albers et al, 2013 ; Smith et al, 2015 ; Yamaura et al, 2018 ; Wang et al, 2021 ). Furthermore, earlier identification of drug-resistant mutations will help better understand the progression of the disease, and enable properly targeted treatment and more durable remissions for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wang P. et al identified and analyzed the in vitro efficacy of a dual oral FLT3 and tubulin inhibitor KX2-391, with very interesting effects on resistant FLT3mut AML cell lines (D835 and F691L). It also effectively reduced leukemic growth of FLT3-ITD-F691L, FLT3-ITD and FLT3-ITD-D835Y mut AML cells in a xenograft leukemia model [ 96 ].…”
Section: Flt3i: Indications Mechanisms Of Resistance In Vitro and In ...mentioning
confidence: 99%